2022
DOI: 10.3390/diseases11010006
|View full text |Cite
|
Sign up to set email alerts
|

Are Drugs Associated with Microscopic Colitis? A Systematic Review and Meta-Analysis

Abstract: There is growing evidence of the association of Microscopic Colitis (MC) with the use of specific medications such as proton pump inhibitors (PPIs), Selective serotonin reuptake inhibitors (SSRIs), Non-Steroidal anti-inflammatory drugs (NSAIDs), Statins and H2-receptor antagonists (H2RA). In our study, we calculated the pooled odds of MC in patients using these drugs. We performed a detailed search of major databases, including PubMed/Medline, Scopus, web of science, and Embase, to include the studies in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…MC noted. The inconsistency in results based on the control group in this PPI and NSAID group warrants our caution in interpreting these results [20].…”
Section: Case Reportmentioning
confidence: 81%
“…MC noted. The inconsistency in results based on the control group in this PPI and NSAID group warrants our caution in interpreting these results [20].…”
Section: Case Reportmentioning
confidence: 81%
“…In studies that have found an association between MC and the use of PPIs and/or statins, the control group has mainly consisted of subjects from the general population; such associations have not been confirmed in control groups that consisted of patients with other causes of chronic diarrhea or in subjects referred for colonoscopy. 8 , 14 The rationale for PPIs and statins as a risk factor for MC are weakly based on current knowledge. First, both PPI 15 and statins 16 have shown anti-inflammatory effects on the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of MC is currently not completely understood although smoking 7 and some drugs 8 have been associated with an increased risk of being diagnosed with MC. In a large Danish study that used data from the Danish Prescription Register, a strong association was found between current proton pump inhibitor (PPI) use and MC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation